2021
DOI: 10.1109/access.2021.3105635
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Random Body Bias Application in FDSOI Cryptosystems as a Countermeasure to Leakage-Based Power Analysis Attacks

Abstract: The research leading to these results has been supported by the Spanish AEI -Agencia Estatal de Investigación -grant number PID2019-103869RB-C33/AEI/10.13039/501100011033, by Secretaria d'Universitats i Recerca of Generalitat de Catalunya and by the European Social Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The provided energy consumption identified numerous nuclei, with several major changes, like the version described in this study suggested by Palma et al [16]. First and foremost, the methodology is applied to diverse multi-core devices and assesses energy at command instead of resource use.…”
Section: Background To the Energy Prediction Modelsmentioning
confidence: 99%
“…The provided energy consumption identified numerous nuclei, with several major changes, like the version described in this study suggested by Palma et al [16]. First and foremost, the methodology is applied to diverse multi-core devices and assesses energy at command instead of resource use.…”
Section: Background To the Energy Prediction Modelsmentioning
confidence: 99%